2022
DOI: 10.3390/jcm11040934
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Neuromuscular Manifestations of COVID-19 and Management of Pre-Existing Neuromuscular Disorders in Children

Abstract: Since the emergence of SARS-CoV-2, several studies have been published describing neuromuscular manifestations of the disease, as well as management of pre-existing pediatric neuromuscular disorders during the COVID-19 pandemic. These disorders include muscular dystrophies, myasthenic syndromes, peripheral nerve disorders, and spinal muscular atrophy. Such patients are a vulnerable population due to frequent complications such as scoliosis, cardiomyopathy, and restrictive lung disease that put them at risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…These assessments, tools, and adaptations should be patient-centric and customized according to factors like disease severity [ 35 , 43 ], comorbidities [ 34 , 49 ], patient age [ 9 , 44 , 48 , 50 ], access to the internet [ 43 , 44 ], and the coadministration of drugs like corticosteroids that are necessary but lower immunity [ 29 , 34 , 36 ]. Additionally, strategies like use of prioritized assessments and protocol flexibility (both encouraged by the FDA during the pandemic) may help ensure trial continuity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assessments, tools, and adaptations should be patient-centric and customized according to factors like disease severity [ 35 , 43 ], comorbidities [ 34 , 49 ], patient age [ 9 , 44 , 48 , 50 ], access to the internet [ 43 , 44 ], and the coadministration of drugs like corticosteroids that are necessary but lower immunity [ 29 , 34 , 36 ]. Additionally, strategies like use of prioritized assessments and protocol flexibility (both encouraged by the FDA during the pandemic) may help ensure trial continuity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, SMA community members had to balance concerns about COVID-19 exposure with the need to access key healthcare services for management of SMA, such as treatment administration and monitoring, physical therapy, and in-home care [ 29 31 ]. While telehealth visits can support continuity of care in some settings, many SMA-related services—such as diagnosis confirmation, drug administration, and physical therapy—still require in-person interaction [ 29 , 32 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that COVID-19 disease might lead to neurological impairment by damaging the central and peripheric nervous system through dysregulated inflammatory stimuli, hypoxia, and direct lesion mechanisms [22]. More in detail, COVID-19 neuromuscular sequelae might be directly or indirectly connected to SARS-CoV-2 infection; hence, a COVID-19 affinity for neural tissue has been proposed, with the direct infection and injury of motor neurons and peripheral nerves reported two to three weeks after infection [23,24]. In accordance, a third of patients with other coronavirus infections complained of myalgia, high creatine kinase (CK) levels, and rhabdomyolysis, suggesting that the infection may induce viral myositis [23,24].…”
Section: Organic and Functional Impact Of Covid-19 On Anterior Crucia...mentioning
confidence: 99%
“…More in detail, COVID-19 neuromuscular sequelae might be directly or indirectly connected to SARS-CoV-2 infection; hence, a COVID-19 affinity for neural tissue has been proposed, with the direct infection and injury of motor neurons and peripheral nerves reported two to three weeks after infection [23,24]. In accordance, a third of patients with other coronavirus infections complained of myalgia, high creatine kinase (CK) levels, and rhabdomyolysis, suggesting that the infection may induce viral myositis [23,24]. Moreover, high levels of LDH were found in subjects with myalgia and fatigue, and elevated levels of myoglobin were documented in severe COVID-19 [25].…”
Section: Organic and Functional Impact Of Covid-19 On Anterior Crucia...mentioning
confidence: 99%
See 1 more Smart Citation